2019
DOI: 10.1108/cdi-06-2017-0093
|View full text |Cite
|
Sign up to set email alerts
|

Early career values and individual factors of objective career success

Abstract: Purpose The purpose of this paper is to investigate the early career values and individual factors of objective career success among graduates from a top-tier French business school. Design/methodology/approach The authors conducted a quantitative analysis of 629 graduates classified in three job markets according to income: the traditional business market, the alternative market and the high-potential business market. The graduation dates span a period of 12 years before the 2008 Recession. Findings The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 195 publications
0
21
0
4
Order By: Relevance
“…In a recent study, Guan et al (2019) found an increase in voluntary mobility across different occupations in France, mainly due to the changing nature of jobs. Giraud et al (2019) study conducted among French business professionals found that employees are actively involved in job-hopping (the practice of making frequent voluntary job changes; Lake et al, 2018), which appears to represent increased protean and boundaryless career mindsets (Lake et al, 2018). Moreover, in France, few studies have been conducted on the relations between PCA, BCA, and career-related outcomes (e.g., Segers et al, 2008), which warrants further examination (Giraud et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Guan et al (2019) found an increase in voluntary mobility across different occupations in France, mainly due to the changing nature of jobs. Giraud et al (2019) study conducted among French business professionals found that employees are actively involved in job-hopping (the practice of making frequent voluntary job changes; Lake et al, 2018), which appears to represent increased protean and boundaryless career mindsets (Lake et al, 2018). Moreover, in France, few studies have been conducted on the relations between PCA, BCA, and career-related outcomes (e.g., Segers et al, 2008), which warrants further examination (Giraud et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Social ties do not only generate social identifications or social credentials, but it also helps to reinforce the individual's identity and recognition (Mao and Shen, 2020; Friedman and Krackhardt, 1997). Recognising an individual's merit not only provides acknowledgement of their claim to certain social resources, but also provides emotional and psychological support which was highly cited by the participants (Giraud et al , 2019). The reinforcement of the individual's identity, emotional support and recognition are indispensable for the individual's mental health preservation (Kaye et al , 2017; Lin, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…By utilising mentoring functions obtained through organisational and management support, mentoring can help regulate the relationship effect between protégé and mentor (Eby & Robertson, 2019;Gyansah & Guantan, 2018). Today's competitive labour market affects employees' ability to obtain the best job opportunities; however, for early-career employees, there is a career value associated with the length of employment in one organisation; therefore, the decision to stay or leave is somewhat dependent on their mentor, who may have an impact on their career future perspectives (Giraud et al, 2019). The interaction between the protégé (particularly the newly employed) and the mentor provides the mentor with direct control over job assignments, career guidance, and job security (Carter & Youssef-Morgan, 2019;Lapointe & Vandenberghe, 2017).…”
Section: The Role Of Mentoring As the Mediator On The Relationship Be...mentioning
confidence: 99%